Kolaborasi Nilai Budaya dan Religi dalam Tradisi Gejug Lesung dan Methik Pari di Desa Glinggang Sampung Ponorogo - Muhamad Nurois Amin Rois; Fatakhul huda Huda (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2022)
Most of the inhabitants of the island of Java work as farmers. This shows that the island of Java has land that is so fertile and prosperous, so it is very suitable to be used for farming activities. The mental attitude of the farmers is formed by the influence of the situation and condition of the place they currently occupy, including environmental and climatic factors such as hot and cold summers which are in line with the dry season and rainy season. The tradition of Methik Pari and gejug Lesung is a tradition handed down by ancestors who are influenced by Hindu-Buddhist religion and believe that Dewi Sri (Javanese) is the Goddess of agriculture, the Goddess of rice and rice fields and the Goddess of fertility on the islands of Java and Bali, she is believed to be as the Goddess who ruled over the underworld realm as well as the moon. Cultural values ​​are values ​​that are agreed upon and embedded in a society, organizational scope, community environment, which are rooted in a habit, belief, symbols, with certain characteristics that can be distinguished from one another as a reference for behavior and responses to what will happen or is happening. Religious values ​​are the values ​​of life that reflect the growth and development of religious life which consists of three main elements, namely aqidah, worship and morals which become behavioral guidelines in accordance with divine rules to achieve prosperity and happiness in life in this world and the hereafter. The metik pari and gejug lesung activities which are carried out together, apart from being an effort to preserve culture, there are also efforts to understand the community so that the community understands the methik pari and gejug lesung activities in the context of expressing gratitude to God Almighty for the sustenance obtained and The joint prayer aimed at Dewi Sri, who is considered the guardian of rice, is essentially a prayer to Allah SWT